Variantes reguladoras associadas à expressão alelo-específica (aseQTL) em músculo de Nelore (Bos indicus) - Bruscadin, Jennifer Jessica (Universidade Federal de São Carlos, 2020)
Brazil is a significant exporter of beef, so the improvement of Nelore, a breed mostly present in the Brazilian herd, directly impact this sector. Genomic tools can identify SNPs associated with interesting livestock phenotypes, but the selection efficiency depends on the expression of the selected alleles in the animals. Previous studies have identified 820 SNPs presenting allelespecific expression (ASE) in Nelore’s Longissimus thoracis muscle, for which we searched for regulatory SNPs associated with this allelic expression pattern, or aseQTLs (allele-specific expression quantitative trait loci). To this end, scans were performed within 1Mb windows from the SNP with ASE (ASE SNP), and subsequently, the candidate genotypes of that window were related to the allelic imbalance in the ASE SNP. For obtaining the methylation profile of aseQTLs, the candidate positions were overlapped with RRBS (Reduced Representation Bisulfite Sequencing) methylation data from 12 animals of the same population. The flanking sequences of aseQTLs were used to predict the allele-specific presence of transcription factor binding sites (TFBSs) and miRNAs. We identified 1,134 aseQTLs associated with 126 ASE SNPs. Sixteen aseQTLs were methylated in our population, 215 affected TFBSs expressed in bovine muscle, and 162 aseQTLs affected miRNA binding sites. The integration of aseQTLs with previous association studies performed in the same population showed enrichment for meat quality traits, such as tenderness, rib eye area, and intramuscular fat. AseQTLs associated with the CMYA5 gene showed high linkage disequilibrium (LD), multiple overlaps with meat quality phenotypes and prediction of binding sites for miRNAs, thus indicating potential regulatory sites for this gene. In general, the results indicate that ASE may be the result of regulation exercised by multiple aseQTLs and undergo modulation by epigenetic and cisregulatory mechanisms. The aseQTLs described had a significant influence of LD. These variants may impact the expression of genes functionally important for phenotypes that affect, among others, meat sensory characteristics, factors that are essential for consumer acceptance.
Regulatory variants associated with allele-specific expression (aseQTL) in Nelore (Bos indicus) muscle
Keywords: Qualidade da carne; Genômica; Epigenética; Mecanismos de regulação; Meat quality; Genomics; Epigenetics; Regulatory mechanisms; CIENCIAS BIOLOGICAS::GENETICA